Possible Benefits of Zinc supplement in CVD and COVID-19 Comorbidity - Muhammad Manjurul Karim; Shahnaz Sultana; Rokaia Sultana; Mohammad Tariqur Rahman (Elsevier, 2021)
As far as comorbidity is concerned, cardiovascular diseases (CVD) appear to be accounted for the highest prevalence, severity, and fatality among COVID 19 patients. A wide array of causal links connecting CVD and COVID-19 baffle the overall prognosis as well as the efficacy of the given therapeutic interventions. At the centre of this puzzle lies ACE2 that works as a receptor for the SARS-CoV-2, and functional expression of which is also needed to minimize vasoconstriction otherwise would lead to high blood pressure. Furthermore, SARS-CoV-2 infection seems to reduce the functional expression of ACE2. Given these circumstances, it might be advisable to consider a treatment plan for COVID-19 patients with CVD in an approach that would neither aggravate the vasodeleterious arm of the renin-angiotensinogen-aldosterone system (RAAS) nor compromise the vasoprotective arm of RAAS but is effective to minimize or if possible, inhibit the viral replication. Given the immune modulatory role of Zn in both CVD and COVID-19 pathogenesis, zinc supplement to the selective treatment plan for CVD and COVID-19 comorbid conditions, to be decided by the clinicians depending on the cardiovascular conditions of the patients, might greatly improve the therapeutic outcome. Notably, ACE2 is a zinc metalloenzyme and zinc is also known to inhibit viral replication.